Determination of Total Tannin Content from Methanol Extracts of Various Species of Ferns (Pteridophyta) - Hariyanti, Weni; Masriani, Masriani; Sasri, Risya; Sapar, Ajuk; Erlina, Erlina; Ersando, Ersando (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Abstract The use of heavy-metal mordants in fabric dyeing is prohibited due to the resulting impacts such as environmental damage and public health, therefore environmentally friendly and non-toxic mordants such as tannin mordants (biomordants) are needed. Based on phytochemical screening on fern species (Pteridophyta), it is known that they contain tannins. However, scientific evidence of determining the total tannin content of various species of ferns has so far not been found. This study aims to determine the yield and total tannin content of methanol extracts of five fern species, namely paku kawat (Lycopodium cernuum), paku resam (Gleichenia linearis), paku dayak (Blechnum orientale), paku uban (Nephrolepis biserrata), paku miding (Stenochlaena palustris). Sample extraction was carried out by maceration method using methanol solvent. Extract yield was determined by weighing method. Analysis of total tannin content was carried out by UV-Vis spectrophotometric method at a wavelength of 755.8 nm using Folin-Ciocalteu reagent and sodium carbonate. The results of the research obtained the yield of methanol extracts on paku kawat, paku resam, paku dayak, paku uban, and paku miding are 11.271%; 8.389%; 4.810%; 3.615%; and 0.854%, respectively. Total tannin levels in methanol extracts of paku kawat, paku resam, paku dayak, paku uban, and paku miding were 0.024% ± 0.002; 0.256% ± 0.029; 0.272% ± 0.037; 0.143% ± 0.019; and 0.022% ± 0.012, respectively. Based on these data, it can be concluded that the methanol extract of paku kawat produces the highest yield while paku dayak produce the highest total tannin content. The results indicate that differences in fern species cause differences in tannin levels.